Implementation of Local Wisdom-Based Early Childhood Education Curriculum to Improve Early Childhood Cultural Identity - Syafnan; Rizki Hafni RAMBE; Irmayani PASARIBU (RADINKA JAYA UTAMA PUBLISHER, 2025)
Early Childhood Education (PAUD) has a strategic role in shaping children's character and cultural identity from an early age. In the midst of increasingly massive globalization, children are increasingly exposed to foreign cultures that can erode their local cultural values. This study aims to analyze the implementation of PAUD curriculum based on local wisdom in the context of formal education and evaluate its impact on strengthening the cultural identity of early childhood. The method used is a literature study by examining various theories, concepts, and relevant previous research results. The results of the analysis show that the integration of local cultural elements such as folklore, regional songs, traditional games, and traditional ceremonies into learning activities can increase children's cultural awareness and shape character based on noble values ​​such as honesty, responsibility, tolerance, and cooperation. The implementation of this curriculum requires careful planning and the involvement of various parties, including educators, parents, traditional leaders, and local communities so that local wisdom values ​​can be optimally internalized in every learning activity. However, the implementation of local wisdom-based curriculum faces various significant challenges, such as limited competence and resources of educators, lack of official guidelines and policy support, minimal involvement of parents and traditional leaders, and competition with the flow of globalization and digital media that distract children. Serious attention is needed from policy makers, adequate teacher training, close collaboration between schools and communities, and the development of learning facilities and infrastructure that support the optimization of this planning.